KEADILAN GENDER DALAM RUMAH TANGGA PERSPEKTIF FATIMA MERNISSI - Bonita Izwany (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
This study entitled “Gender Justice In Household of Fatima Mernissi's Perspective”. This study aims to know the background and the problem statement from Fatima Mernissi’s thought, to know Fatima Mernissi's view about the position and the role of woman and man, and to analyze Fatima Mernissi’s concept with Islam concept. The author used an interpretation method to analyze the data, and the form of this study is a Library Research. The data used by the authors in this study were divided into primary and secondary data. The primary data used as sources of reference are the book ‘The Veil and The Male Elite: A Feminist Interpretation of Women's Right in Islam’ and the book ‘The Forgotten Queens of Islam’ which are the work and thought of Fatima Mernissi. While the secondary data are the books and the internet media related to the topic of discussion. From the study, it can be concluded that Fatima Mernissi is a person who suggested a review of the actual Islamic concept of the role of women and men especially in the household since she found a tendency of patriarchal cultural influence from ‘ulama in translating the message of Islam. Fatima Mernissi also voiced the importance of women's struggle itself in striving for life to achieve a better quality of life without forgetting their nature as women. Thus it can be concluded that the concept obtained is the concept of gender justice according to Islam and analysis of balanced and mutually compatible Fatima Mernissi’s thought. Women are not restricted to the doctrines that restrict women in their scope. So, the whole idea of Fatima Mernissi is started from the effort to find the point of the problem faced by women, and to reassert women's position from patriarchal and misogyny biases. Women's issues must be addressed at this time, women must rise and use the guarantee of freedom provided. With the best, especially show the identity of women to become a leader because women are equal to men.